Saves the future - Patterson, James; Grabenstein, Chris; Johnson, Beverly (London Young Arrow, 2020)
Now Max and her friends are back and ready to take on their boggest problem yet: world hunger while the change makers tackle this huge issue, Max must also avoid the evil corp and her nemesis, Dr Zimm
Authers of the No. 1 New York times bestseller Max Einstein : the genius experiment
English stories
Keywords: Action and adventure fiction; English stories